Customer Relationship Management (CRM) dan Penanganan Keluhan Pelanggan Restoran D - Putri, Banafsha Shafa Kurnia; Erdiansyah, Rezi (Kiwari, 2025)
Restaurants require competent, customer-oriented workers who are able to provide solutions to customer needs and problems quickly and accurately. This study aims to analyze Customer Relationship Management (CRM) in handling customer complaints, using D Restaurant Jakarta as a case study. The research employs a quantitative approach with a survey method involving 82 restaurant customers as respondents. Data were collected through questionnaires designed to measure the effectiveness of CRM communication, document analysis, and literature review. The sample size was determined using Hair et al.'s (2010) formula, N x 5, resulting in 8 indicators x 10 = 80 respondents. A total of 82 respondents were analyzed without any exclusions. The analysis used listwise deletion, ensuring only complete data for all variables were included. The hypotheses tested are: Hₐ (Alternative Hypothesis), stating that CRM has a positive and significant impact on handling customer complaints, and H₀ (Null Hypothesis), stating that CRM does not have a significant impact on handling customer complaints. The results indicate that the alternative hypothesis is accepted, with CRM having a positive and significant impact on handling customer complaints. The R Square value of 0.452 shows that 45.2% of the variability in complaint handling is explained by CRM. Additionally, the Pearson correlation of 0.672 demonstrates a strong relationship between CRM and the effectiveness of handling customer complaint. Restoran memerlukan tenaga kerja yang kompeten, berorientasi pada pelanggan, dan mampu memberikan solusi atas kebutuhan maupun masalah pelanggan dengan cepat dan tepat. Penelitian ini bertujuan untuk menganalisis manajemen hubungan Pelanggan (Customer Relationship Management) CRM ketika menangani keluhan pelanggan dengan studi kasus pada Restoran D Jakarta. Dalam penelitian ini, pendekatan kuantitatif diterapkan, dan 82 pelanggan restoran digunakan sebagai responden. Dokumen analisis dan studi kepustakaan, serta kuesioner yang dirancang untuk mengukur efektivitas komunikasi CRM, digunakan untuk mengumpulkan data. Untuk menghitung ukuran sampel, Hair et al. (2010) menggunakan formula N x 5, yang menghasilkan 8 indikator x 10 = 80 responden. Tanpa kasus yang dikeluarkan, total 82 responden dianalisis. Karena analisis dilakukan secara listwise, sehingga hanya data yang lengkap untuk semua variabel yang digunakan Hipotesis yang diajukan adalah Hₐ (Hipotesis Alternatif), dimana CRM memiliki pengaruh positif dan signifikan terhadap penanganan keluhan pelanggan, dan H₀ (Hipotesis Nol), dimana CRM tidak memiliki pengaruh signifikan terhadap penanganan keluhan pelanggan. Hasil penelitian menunjukkan bahwa hipotesis alternatif diterima, di mana CRM berpengaruh positif signifikan terhadap penanganan keluhan pelanggan dengan nilai R Square sebesar 0,452, menunjukkan bahwa 45,2% variabilitas penanganan keluhan dijelaskan oleh CRM. Korelasi Pearson sebesar 0,672 menunjukkan hubungan yang kuat antara CRM dan efektivitas penanganan keluhan pelanggan.